Modeling of an Integrated Traction Motor Protection System - Manafov, E. K.; Huseynov, F. H. (Science and Transport Progress, 2024)
Purpose. The article is devoted to the creation of traction motor protection by modern methods and means based on a programmable logic controller (PLC). Methodology. To simulate motor fault monitoring in laboratory conditions, magnetic field and temperature sensors were installed on a small powerful induction motor, and then the data obtained from the sensors in normal and overloaded motor modes were analyzed. Based on the research, protection methods were developed. Findings. Previously used simple motor protection systems based on components such as timers, contactors, electromagnetic switches, voltage and current transformers were slow and inaccurate, and had low sensitivity. However, the production of PLCs and their application in this industry has eliminated these problems. The intensive operation of motors as the main executive equipment requires the creation of modern automated protection systems to ensure their reliable and stable operation. Originality. The paper improves the method of protection of traction motors based on the use of programmable logic controllers. In addition to the voltage and current parameters, the proposed method involves monitoring the magnetic field. It also provides for the possibility of adjusting the protection response time. As a result, in the event of overload, short circuit, and other non-standard situations, the improved method provides the system with the ability to make more accurate and reliable decisions. Practical value. The TIA Portal software package has modeled a traction motor protection system by temperature and current and considered its practical application. To make such systems more effective, in the future, comprehensive protection systems based on the diagnostic state of the traction motor can be developed. In addition, an effective system can be created by providing SCADA control of the engines of several vehicles simultaneously.